Not Str8: the Construction of Queer Male Identity in Sydney, Australia - John P. Egan (Adult Education Research Conference, 2004)
This study examines the experiences of 14 queer young men in Sydney Australia. Using ethnographic methods, their stories are analyzed to delineate how their experiences “coming out” and coming into a queer male identity represents the acquisition and meaning-making of genuinely local, transgressive knowledges.